The position of da’wah messages and ethics in Malaysian and Indonesian television programs - Siagian, Haidir Fitra; Mustari; Fauziah Ahmad (Penerbit Universiti Kebangsaan Malaysia, 2016)
Rapid changes in the whole aspects of our lives as a result of the global development need to be addressed by spreading da’wah messages through television channels. To be an effective da’wah media, television should have a strong editorial policy. The policy forwarded could prove the dynamic representation of the country. This study aims to explore the editorial policy of TV Malaysia and Indonesia in presenting da’wah programs, and secondly, to understand the position of ethics in the da’wah messages broadcast on Malaysian and Indonesian TVs. By using qualitative methods, the data have been derived from direct observations and interviews with three television stations in Malaysia (two government-owned and one private-owned TVs) and TVRI and RCTI in Indonesia. Data are also enriched by relevant information from watching Malaysian and Indonesian TV channels. The results showed similarities and differences between the TV editorial policies of the two countries. Respondent from both countries showed that they tried to attract viewers through providing various kinds of religious broadcasts and carefully considered what they should show on prime time. The different thing is the determination of the da’i and program duration. On Malaysian television, determination of the religious speakers is very strict, whereas in Indonesia determination television speakers tend to be rather easy. In terms of duration, the whole da’wah broadcasts per day on Malaysian television are longer and are more frequent than that on the Indonesian’s. In Malaysia, the programs are decided to be on schedule for prime time while in Indonesia the da’wah programs are mostly not in the prime time.